1999
DOI: 10.1589/jpts.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visual Feedback on Muscle Endurance in Normal Subjects

Abstract: Abstract. The measurement of maximum voluntary isokinetic contraction is a common practice in research and clinical settings. The purpose of this study was to investigate the effect of visual feedback on muscle endurance. Subjects were 22 male, between the ages of 18 and 31. Each subject had no history of lower extremity joint injury, surgery, or disease. All subjects completed two isokinetic exercise test sessions. The tests consisted of 50 maximum voluntary isokinetic contractions, using dynamometer (KIN-COM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…MET can assess the ability to resist fatigue by measuring the maximal duration while exerting a force at a specific level until failure. A large amount of effort has been contributed to developing MET models for different muscle groups under different static working conditions (Rohmert, 1960(Rohmert, , 1973Rohmert et al, 1986;Bishu et al, 1995;Kanemura et al, 1999;Mathiassen and Ahsberg, 1999;Garg et al, 2002;Law and Avin, 2010). Although the MET models can predict the maximum endurance time under a given relative force level, the decrease in the muscular strength cannot be predicted directly by MET models.…”
Section: Introductionmentioning
confidence: 99%
“…MET can assess the ability to resist fatigue by measuring the maximal duration while exerting a force at a specific level until failure. A large amount of effort has been contributed to developing MET models for different muscle groups under different static working conditions (Rohmert, 1960(Rohmert, , 1973Rohmert et al, 1986;Bishu et al, 1995;Kanemura et al, 1999;Mathiassen and Ahsberg, 1999;Garg et al, 2002;Law and Avin, 2010). Although the MET models can predict the maximum endurance time under a given relative force level, the decrease in the muscular strength cannot be predicted directly by MET models.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown many EMG measurements, which were used as diagnostic [36,38-41] and/or therapy methods [25,31,42,43]. Selection of the vastus medialis muscle was based on Jarvela [44], who reported that the inferior fibres of vastus medialis are the most important for dynamic knee stability and the reduced load of passive knee structures.…”
Section: Discussionmentioning
confidence: 99%